Effects of worksite exercise intervention (PRODET®) on well-being at work and capability in performing work-related sedentary tasks: A pilot study. - Díaz-Benito, Vıctor Jiménez; Barriopedro Moro, Marıa Isabel; Clemente Remón, Ángel Luis; Santacruz Lozano, José Antonio; Hervás Pérez, Juan Pablo; Vanderhaegen, Frederic (Work, 2022)
BACKGROUND: Companies have tried to carry out interventions in order to mitigate the risks associated with losses in productivity and the health of employees. OBJECTIVE: This intervention trial evaluated the effect of a supervised exercise intervention based on aerobic capacity and strength on well-being at work and capability in performing work tasks. METHODOLOGY: The sample was composed of 67 participants (N = 67, mean age 34.31 years) and investigated a 12-week group physical exercise program in the workplace, two days per week for 50 minutes, which was supervised and based on aerobic endurance and strength. The 67 subjects were working-age office workers, deemed sedentary and randomized into an intervention (N = 40) or control (N = 27) group. Among them, 33 were men (N = 33; 49.25%) and 34 were women (N = 34, 50.75%). Outcomes were assessed pre- and post-test in both groups. The Mann-Whitney U and Chi-Square tests were performed to compare the characteristics of the intervention and control group. η2 = z/(n-1) was calculated as effect size rates. RESULTS: The program showed statistically significant effects on strength endurance (P = 0.020, η2 = 0.08), the loss of fat percentage (P = 0.015, η2 = 0.09), lower limb power (P = 0.020, η2 = 0.08) and QoL (P = 0.0001, η2 = 0.39 for the physical health outcome, and P = 0.0001, η2 = 0.35 for the outcome of total scores of mental health). CONCLUSIONS: The intervention had an impact on the endurance, fat percentage loss and QoL of the workers whose occupations were based on sedentary tasks.